2016
DOI: 10.1037/xge0000197
|View full text |Cite
|
Sign up to set email alerts
|

The nature of semantic priming by subliminal spatial words: Embodied or disembodied?

Abstract: Theories of embodied semantics (ES) suggest that a critical part of understanding what a word means consists of simulating the sensorimotor experience related to the word's referent. Some proponents of ES have suggested that sensorimotor activations are mandatory and highly automatic during semantic processing. Evidence supporting this claim comes from masked priming studies showing that unconsciously perceived spatial words (e.g., up, down) can directly modulate action performance on the basis of their meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 75 publications
(164 reference statements)
5
12
0
1
Order By: Relevance
“…As we did not see such pattern, and we have moreover evidence from our dialogues with patients (see Appendix in Supplementary Material) that they fully understand the meaning of VPs (indeed of whole sentences), we conclude that VP semantics is largely spared in ALS. Our data side with Papeo et al (2015b) in providing indirect evidence for the relative independence of V or VP semantics from representations and processes residing within the motor system (for recent work challenging the embodied hypothesis, see Pavan and Baggio, 2013; Pavan et al, 2013; Papeo et al, 2015a; Bottini et al, 2016; Ghio et al, 2016; Areshenkoff et al, 2017). …”
Section: Discussionsupporting
confidence: 81%
“…As we did not see such pattern, and we have moreover evidence from our dialogues with patients (see Appendix in Supplementary Material) that they fully understand the meaning of VPs (indeed of whole sentences), we conclude that VP semantics is largely spared in ALS. Our data side with Papeo et al (2015b) in providing indirect evidence for the relative independence of V or VP semantics from representations and processes residing within the motor system (for recent work challenging the embodied hypothesis, see Pavan and Baggio, 2013; Pavan et al, 2013; Papeo et al, 2015a; Bottini et al, 2016; Ghio et al, 2016; Areshenkoff et al, 2017). …”
Section: Discussionsupporting
confidence: 81%
“…What is the role of modality-specific simulations, like the one elicited in visual cortices in the sighted, during conceptual retrieval? It has been suggested that modalityspecific representations may not always be necessary during conceptual retrieval and could instead be related to processing demands (Ostarek & Huettig, 2017;Bottini, Bucur, & Crepaldi, 2016). For instance, visual representations of low-level characteristics of objects may not be activated when a shallow processing such as a lexical decision (Ostarek & Huettig, 2017) or an orthogonal conceptual task (e.g., judging semantic relatedness; Martin, Douglas, Newsome, Man, & Barense, 2018) is required.…”
Section: Discussionmentioning
confidence: 99%
“… 7. Note, however, that even masked priming effects can be modulated by task requirements (Duñabeitia et al, 2011; Marelli et al, 2013), list composition (Feldman & Basnight-Brown, 2008), and can sometimes capture semantic information (e.g., Bottini et al, 2016). …”
mentioning
confidence: 99%